Treatment of Cicatricial Lower Eyelid Ectropion with Suture of Horner Muscle Combined with Fascia Transplantation - Kento Takaya, MD, PhD; Shigeki Sakai, MD, PhD; Kazuo Kishi, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. This case series aimed to describe a new technique for correcting contractures and deformities that reliably addresses lacrimal punctum deviation and severe cicatricial lower eyelid ectropion. This was a technical description and a retrospective interventional case series. Eyelid ectropion and lacrimal punctum deviation were treated surgically by grafting the fascia lata and suturing the tarsus-Horner muscle. In total, three patients underwent this surgery: one for burns, one for lower eyelid tumor resection, and the other for an orbital floor fracture following a motorcycle accident, all resulting in ectropion. All patients previously had failed ectropion correction procedures, including scar revision, skin grafting, auricular cartilage grafting, and lateral tarsal strips. The mean follow-up was 15.8 (12.5–18.5) months. Furthermore, all patients showed resolution of lower eyelid ectropion and significant improvement in lower eyelid contracture, with a mean increase of 4.0 (2.5–5) mm. No severe complications were observed, and they reported a significant improvement in ocular surface symptoms. Our study shows that tacking of the tarsus and Horner muscles in combination with fascia lata grafting is effective in correcting refractory cicatricial lower eyelid ectropion with deviation of the tear punctum.